2017
DOI: 10.1177/0049475517711017
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous epididymo-orchitis: diagnosis by fine needle aspiration

Abstract: Tuberculosis is the leading cause of chronic granulomatous epididymo-orchitis in the Asian population. A retrospective analysis of 40 patients diagnosed with granulomatous or tubercular epididymo-orchitis on fine-needle aspiration (FNA) was carried out. May Grünwald giemsa, haematoxylin and eosin and Ziehl Neelsen stained smears were evaluated. Of 40 patients studied, aspiration smears showed epithelioid cell granulomas with caseation in 17, granulomas alone in 19 and caseation only in four. Acid fast bacilli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Besides looking for bacteriological evidence, another de nitive examination of epididymitis TB is FNAB cytology or surgical resection of the epididymis. 22 FNAB has an essential role in excluding the differential diagnosis of epididymal nodules, such as malignancy, or other benign tumors, both acute and chronic. 12,21,22 FNAB can provide an accurate and rapid diagnosis and prevent aggressive and potentially inappropriate surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides looking for bacteriological evidence, another de nitive examination of epididymitis TB is FNAB cytology or surgical resection of the epididymis. 22 FNAB has an essential role in excluding the differential diagnosis of epididymal nodules, such as malignancy, or other benign tumors, both acute and chronic. 12,21,22 FNAB can provide an accurate and rapid diagnosis and prevent aggressive and potentially inappropriate surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…22 FNAB has an essential role in excluding the differential diagnosis of epididymal nodules, such as malignancy, or other benign tumors, both acute and chronic. 12,21,22 FNAB can provide an accurate and rapid diagnosis and prevent aggressive and potentially inappropriate surgical procedures. 12,22 However, invasive biopsy is often not feasible to perform, so radiological examination can help establish the diagnosis of epididymitis TB.…”
Section: Discussionmentioning
confidence: 99%
“…Handa et al and Gupta et al, in their retrospective analysis of a combined more than 250 patients, found FNAC useful in 90% cases for a diagnosis of tuberculous orchitis [14][15]. Viswaroop et al reported a case series of 40 patients with epididymal tuberculosis in which 26 patients diagnosed with FNAC, nine patients required tissue biopsy, and five patients underwent orchiectomy for the suspicion of a testicular tumor and diagnosed with histopathology specimen [16].…”
Section: Discussionmentioning
confidence: 99%
“…С целью гистологической верификации диагноза некоторые авторы (N. Gupta et al, U. Handa et al) считают полезным выполнять тонкоигольную биопсию, однако эта процедура потенциально опасна, т. к. может вызвать у нелеченого больного молниеносную генерализацию туберкулеза [55,56]. Кроме того, в дифференциально-диагностическом ряду на первом месте стоит злокачественная опухоль яичка, поэтому ряд авторов предпочитают выполнить расширенную орхэктомию без предварительной биопсии, чтобы избежать диссеминации не только инфекции, но и опухолевых клеток [57].…”
Section: диагностика туберкулеза яичка и его придаткаunclassified